Catering planner Manajemenacar dan Catering Berbasis Web Pada PT Mitra Kartika Nuswantara - Farandika, Reyvanza Atalla; Julivano, Ficky Chikara; fauzi, Amir Hasanudin (eProceedings of Applied Science, 2025)
Abstract—PT Mitra Kartika Nuswantara is a company that provides catering and event management services. Manual processes in managing orders, schedules, and inventory often result in inefficiencies and miscommunication. This study proposes the development of a web-based application named Catering Planner to support the digital transformation of the company’s operations. The system was developed using Laravel and MySQL and includes role-based access for admins and staff. Admin users are able to manage orders, inventory, reports, and event schedules, while staff users are limited to viewing assignments. A needs analysis was conducted through interviews and observations involving operational and administrative staff. Functional requirements include order and inventory management, scheduling, reporting, and user access control. The system is designed with an intuitive interface, offering features such as a login page, a dashboard with data visualization, order and inventory forms, and reporting modules. Functional testing using black-box and Selenium methods confirmed the reliability of the system. Additionally, user testing using a Likert scale indicated an overall satisfaction rate of 81.09%. This application is expected to enhance operational efficiency, reduce manual errors, and serve as a scalable solution for future system expansion. Keywords— Web application, Laravel, catering management, inventory system